The Political Configuration of Historical Narrative: The Case of Kazakhstan. (3rd July 2018) - Shlapentokh, Dmitry
ABSTRACT: As time has progressed, Russia has shed the historical legacy of the Soviet era. The same process is going on in Central Asia. The obliteration of the Soviet historical legacy reflects the dying out of the memories of the Soviet Union and the very fact that all these countries had been parts of one state in the not-so-distant past. At the same time, some of these states started to engage in bitter rivalry. The historical legacies were adjusted to new realities. Here, two models compete: one could be called "Turkic" and the other "Iranian." The "Turkic" model implies that Turkic people are truly autokthonous and have lived in Central Asia since the Bronze Age, and that Iranians/Indo-Europeans are newcomers, without much legitimacy. The "Iranian" model implies that it is Iranians/Indo-Europeans who are truly autokthonous people of Central Asia, and creators of the ancient culture. At the same time, Turkic people are nothing but destructive brutes. Meanwhile, China increasingly fills the discursive and geopolitical vacuum.